The Study of the Sacrifice and Beliefs of the Royal Ploughing Ceremony in Joseon Dynasty - Yinsen, Parit; แสงทอง, พิเชฐ (Journal of International Studies, Prince of Songkla University, 2024)
The purpose of this article is to study the Royal Ploughing ceremony from the chronicles of Jeseon and related documents. It focuses on the beliefs related to the agricultural way of life of the Jeseon people. The study found diverse beliefs reflecting a society rooted in agriculture, closely connected to nature and the supernatural. However, the beliefs in these customs and rituals also showcase the role of the monarch in sustaining the livelihood of the subjects, highlighting societal divisions. The state uses the Royal Ploughing ceremony as a special platform to demonstrate that people from different social strata share in the hopes of a bountiful agricultural yield.